SOME PROCEDURAL ISSUES RELATED TO THE PARTICIPATION OF AN INTERPRETER AS A PERSON ASSISTING IN THE ADMINISTRATION OF JUSTICE IN CIVIL PROCEEDINGS - Davlatjon Khabibullayev; P. T. Yesenbekova (European Science Publishing, 2024)
This article presents a scientific and theoretical analysis of the issues of improving the procedural norms related to the participation of the interpreter as a person assisting in the administration of justice in civil proceedings. Also, the procedural rights and obligations of the interpreter in the civil process, the expenses paid to him, and the civil procedural laws of foreign countries were compared with the national civil procedural laws. Scientific-theoretical conclusions, proposals and recommendations aimed at improving the norms related to the participation of an interpreter in civil proceedings have been put forward.
Keywords: civil proceedings, justice, interpreter, persons contributing to the administration of justice, court on civil cases, the principle of the language in which court cases are conducted.